Respuesta :
Answer:
Step-by-step explanation:
x = first number, y = second number
4x - 3y = 12
2x + 3y = 6
------------------add
6x = 18
x = 18/6
x = 3
4x - 3y = 12
4(3) - 3y = 12
12 - 3y = 12
-3y = 12 - 12
-3y = 0
y = 0
solution : (3,0)
By using the elimination method, the first number is 3 and the second number is 0.
- Let the first number be a.
- Let the second number be b.
Translating the word problem into an algebraic expression, we have;
Four times one number minus three times another number is 12:
[tex]4a -3b=12[/tex] ...equation 1.
Two times the first number added to three times to the second number is 6:
[tex]2a+3b=6[/tex] ...equation 2.
Applying the elimination method, we have:
[tex](4a+2a)+(-3b+3b)=12+6\\\\6a=18\\\\a=\frac{18}{6}[/tex]
a = 3
For the value of the second number:
[tex]2a+3b=6\\\\2(3)+3b=6\\\\6+3b=6\\\\3b=0\\\\b=0[/tex]
Read more on elimination method here: https://brainly.com/question/489689